Wogonin Induces Apoptosis and Reverses Sunitinib Resistance of Renal Cell Carcinoma Cells via Inhibiting CDK4-RB Pathway - Wang, Yong; Chen, Shouzhen; Sun, Shuna; Liu, Guangyi; Chen, Lipeng; Xia, Yangyang; Cui, Jianfeng; Wang, Wenfu; Jiang, Xuewen; Zhang, Lei; Zhu, Yaofeng; Zou, Yongxin; et al. (Frontiers in Pharmacology, 2020)
Wogonin, an active component derived from Scutellaria baicalensis, has shown anti-tumor activities in several malignancies. However, the roles of wogonin in RCC cells remain elusive. Here, we explored the effects of wogonin on RCC cells and the underlying mechanisms. We found that wogonin showed significant cytotoxic effects against RCC cell lines 786-O and OS-RC-2, with much lower cytotoxic effects on human normal embryonic kidney cell line HEK-293 cells. Wogonin treatment dramatically inhibited the proliferation, migration and invasion of RCC cells. We further showed that by inhibiting CDK4-RB pathway, wogonin transcriptionally down-regulated CDC6, disturbed DNA replication, induced DNA damage and apoptosis in RCC cells. Moreover, we found that the levels of p-RB, CDK4 and Cyclin D1 were up-regulated in sunitinib resistant 786-O, OS-RC-2 and TK-10 cells, and inhibition of CDK4 by palbociclib or wogonin effectively reversed the sunitinib resistance, indicating that the hyperactivation of CDK4-RB pathway may at least partially contribute to the resistance of RCC to sunitinib. Together, our findings demonstrate that wogonin could induce apoptosis and reverse sunitinib resistance of RCC cells via inhibiting CDK4-RB pathway, thus suggesting a potential therapeutic implication in the future management of RCC patients.